Filsafat Pendidikan Islam Sebagai Basis Integrasi Ilmu Pengetahuan - Tsabita Salsabila; Susantrin; Muhammad Jimmi (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2026)
Islamic Educational Philosophy as the Basis for the Integration of Knowledge. The aim of this research is to examine the Philosophy of Islamic Education which plays a role as a conceptual basis in integrating knowledge and overcoming the dichotomy between religious knowledge and general knowledge in the modern education system. Method: This research employs a qualitative approach using library research. Data were collected from various academic sources such as books, journals, and scholarly articles, and then analyzed using a descriptive-analytical method to identify concepts, patterns, and the relevance of knowledge integration from the perspective of Islamic educational philosophy. Findings: The results show that Islamic educational philosophy offers a holistic and integrative framework based on the principle of tauhid, integrating sources of knowledge derived from revelation, reason, and empirical experience. The integration of knowledge encompasses not only epistemological aspects but also axiological dimensions that emphasize moral values and social responsibility. The implementation of knowledge integration can be carried out through an integrated curriculum, learning processes that incorporate spiritual values, the holistic role of educators, and a supportive educational environment. Therefore, Islamic educational philosophy plays a strategic role in developing a holistic education system capable of producing individuals who are balanced in intellectual, spiritual, and moral dimensions.